Case Study Of Shoprite Holdings Ltd - Najjingo, Sheilah Muwanga (2007)
Shoprite holdings limited is the largest food retailer in Africa and employs about 65,000 employees in all its operations in the RSA and outside South Africa. The shoprite group of companies is an investment holdings company whose combined subsidiaries constitute the fastest moving consumer goods retail operations on the continent. Its various chains operate a total of 840 stores in 17 countries, all integrated electronically into a central base and replenishment system.